Simulation of pedestrian movements using a fine grid cellular automata model - Siamak Sarmady; Fazilah Haron; Abdullah Zawawi Talib (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
Crowd simulation is used in evacuation and crowd safety inspections and in the study of the performance of crowd systems and animations. Cellular automata are extensively utilized in crowd modeling. In regular cellular automata models, each pedestrian occupies a single cell with the size of a pedestrian body. The movements of pedestrians resemble those of chess pieces on a chessboard because the space is divided into relatively large cells. Furthermore, all pedestrians feature the same body size and speed. This study proposes a fine grid cellular automata model that uses small cells and allows pedestrian bodies to occupy several cells. The model allows the use of different body sizes, shapes, and speeds for pedestrians. The model is also used to simulate the movements of pedestrians toward a specific target. A typical walkway scenario is considered to test and evaluate the proposed model. Pedestrian movements are smooth because of the fine grain discretization of movements, and simulation results match the empirical speed–density graphs with good accuracy.